Ionic mass transfer in channel electrodes under laminar flow - Palade de Iribarne, A. (1970)
The rate of ionic mass tranfer under a Poiseuille profile in channel electrodes involving inert zones has been studied. The electrolysis cell was vertically and horizontally placed, the working electrodes facing either upwards or downwards. An extension of Levich's solution for the convective-diffusion equation in a tube comprising an inert zone was applied. The experimental numerical coefficient lies 10% lower than the one theoretically derived.